The emergence of transnational hybrid governance: how private risks trigger public intervention (2020)
The wave of financial market regulations that followed the financial crisis of 2008 offers new insights for understanding the conditions under which public regulators intervene in privately self-regulated markets and the possible forces containing their actions. The legislative and regulatory initiatives that were taken in the EU between 2009 and 2018, in fact, extended the reach of public regulation into areas that were previously mostly regulated through privately set standards. However, as the new rules and regulations do not affect all aspects of the financial markets in the same way, they provide a considerable degree of within-case variation in terms of the extent to which certain segments of the market are affected by – or remain exempt from – the extension of public oversight. This within-case variation is highly useful in providing a deeper insight into whether – and under which conditions – private self-regulation prompts (centralised) public regulation (H8). In this chapter, by investigating the interaction between private and public regulators during the post-crisis regulatory wave, we probe the plausibility of our hypotheses about how systems of hybrid governance emerge and develop.